PELATIHAN PENGEMBANGAN SUMBER DAYA MANUSIA PEGIAT PARIWISATA MATA AIR SIRAH PEMALI - Wibowo, Ugung Dwi Ario; Utami, Paramita Prasetia (Universitas Muhammadiyah Tangerang, 2021)
This community service aims: to be able to help the management of the Sirah Pamali Spring tourist attraction, Winduaji village, Paguyangan District, Brebes Regency understand the potential of tourism human resources and understand consumer psychology in an effort to segment the Sirah Pamali tourism object market. This community service uses a subject of 21 participants from various elements supporting Sirah Pamali tourism. The material for community service is to introduce and practice various things, including: (1) reorienting tourism during the pandemic and post-pandemic period; (2) recognize the concept of market segmentation; (3) identify consumer needs for tourism market mapping and marketing design; and (4) implementation of consumer psychology in an effort to promote tourism in Sirah Pamali Springs. Implementation of the training, with lectures, discussions, and simulation-practice methods accompanied by feedback. In conclusion, the Training of Human Resources Development for Tourism Activists of Sirah Pemali Springs is very appropriate to be applied as an effort to form understanding and readiness of tourism activists through human resource development training. Follow up. Post-training assistance in the field/workplace and simulations in the development of human resources for tourism activists in Sirah Pamali Springs